Temperature and Heat Module with Guided Inquiry Model to Improve Student Learning Outcomes - Sultan Syekh Nuhly Rifa Rizkya Robby Hidayatullah; Mastuang Mastuang; Saiyidah Mahtari (Universitas Lambung Mangkurat, 2026)
The persistently low learning outcomes in physics indicate that students frequently struggle to analyze experimental results in depth—a challenge often exacerbated by conventional teacher-centered instructions. This study developed and evaluated a temperature and heat instructional module integrated with the Guided Inquiry model to enhance student learning outcomes. Employing the ADDIE development framework, the study involved 33 eleventh-grade students at SMA Negeri 1 Angsana as test subjects. Data were gathered using validation instruments, implementation observation sheets, and a learning outcome test, analyzed through quantitative descriptive statistics. The results demonstrated high product validity, with a score of 3.47 and a high reliability coefficient of 0.68. The module exhibited exceptional practicality, achieving a 92% implementation rate. Regarding effectiveness, the module yielded a moderate improvement in learning outcomes, evidenced by an average normalized gain (N-gain) of 0.57. Post-intervention analysis showed that while cognitive scores substantially increased, the formal mastery rate reached 30.3% (10 students), with 69.7% (23 students) still developing proficiency due to persistent algorithmic calculation bottlenecks. It is concluded that the guided inquiry module is valid, highly practical, and moderately effective, serving as a structured pedagogical alternative to bridge conceptual understanding and experimental inquiry in resource-limited physics classrooms.